Instagram Based Reading Strategies Improve Students’ Comprehension Skills - Yupiter, Piju; Pratama, Yoga; Wahyuni, Sri (Pedagogia : Jurnal Pendidikan, 2025)
This study aimed to investigate the effectiveness of using Instagram as a social media platform to enhance students’ reading comprehension among tenth-grade students at SMK 02 Empat Lawang. The research employed a quasi-experimental design involving two groups: an experimental class taught using Instagram and a control class taught through conventional methods. The participants consisted of 62 students, divided equally between the two groups. Data were collected through pre-tests and post-tests comprising 40 multiple-choice questions related to narrative texts. Statistical analysis, including paired sample t-tests and independent t-tests, revealed a significant improvement in reading comprehension in the experimental class compared to the control class. The mean post-test score of the experimental group (75.40) was significantly higher than that of the control group (54.67), indicating that integrating Instagram into reading instruction effectively enhanced students’ engagement and comprehension. The findings suggest that incorporating social media, particularly Instagram, into educational practices can serve as a powerful tool for improving language skills in the digital age. Highlights: Innovative use of Instagram for reading narrative texts. Significant improvement in students’ post-test scores. Suggests Instagram’s pedagogical value in digital learning. Keywords: Instagram, Reading Comprehension, Social Media, Narrative Text, Digital Learning